Development of Pomegranate Juice Blended Tender Coconut Water Beverage - O. P. Chauhan; Asha Singh; P. S. Raju; A. S. Bawa (International Coconut Community Journal, 2008)
Pomegranate juice blended tender coconut water ready-to-serve beverage was developed. Response surface methodology was employed to optimize the levels of dependent variables (levels of tender coconut water, pomegranate juice, TSS and citric acid concentration). The responses studied were sensory (colour, flavour, consistency, mouthfeel and overall acceptability), pH and objective CIE colour values (L*, a*, b*). A Central Composite Rotatable Design (CCRD) was used with six experiments at the central point. The data obtained were analysed employing multiple regression technique to generate suitable mathematical models. Quadratic polynomial models were found to fit well in describing the effect of variables on the responses with high correlation coefficients (R2 87.62 – 99.76), showing the adequacy of the models. An optimum level of the dependent variables (tender coconut water 6.54%, pomegranate juice 6.97%, TSS 12.80 Brix and citric acid 0.12%) was achieved through response surface models for getting optimum values of the responses. The experimental and predicted values at optimum conditions showed high correlation coefficients. The beverage prepared at optimum conditions of the variables showed a shelf life of 6 months at 5, 25 and 350C under packed condition.